Spectrophotometric and Voltammetric Studies on the Interaction of 7-Ethyl-10-hydroxycamptothecin (SN-38) as the Metabolized Compound of CPT-11 with ds-DNA - Hajian, Reza; H. Tan, Guan (Asian Journal of Chemistry, 2012)
The interaction of 7-ethyl-10-hydroxycamptothecin (SN-38) and double stranded DNA (ds-DNA) was studied by absorption spectroscopy and cyclic voltammetry at different temperatures. The results revealed that double stranded-DNA caused the hypochromicity of SN-38 absorption spectra at 384 nm. The binding constant Kb and the number of binding sites n, corresponding thermodynamic parameters between SN-38 and double stranded-DNA at different temperatures were calculated. In addition, the van't Hoff plot of 1/T versus ln Kb suggests that the SN-38 binds endothermically to double stranded-DNA, which is characterized by large positive enthalpy and entropy changes. The Kb at a low concentration of salt is dominated by electrostatic interaction (99.9 %) while that at a high concentration of salt is weakly controlled by non-electrostatic processes (2.23 %). The intercalation of SN-38 with DNA produces an electrochemically inactive macromolecule complex and the peak current of SN-38 was decreased upon the addition of double stranded-DNA molecules. The diffusion coefficients of SN-38 in the absence and presence of double stranded-DNA was calculated as 4.64 × 10-4 and 4.23 × 10-4 cm2 s-1, respectively.